Thyroid gland invasion in advanced squamous cell carcinoma of the larynx and hypopharynx, - Mangussi-Gomes,João (2017)
Abstract Introduction: Squamous cell carcinoma of the larynx and hypopharynx has the potential to invade the thyroid gland. Despite this risk, the proposition of either partial or total thyroidectomy as part of the surgical treatment of all such cases remains controversial. Objectives: To evaluate the frequency of invasion of the thyroid gland in patients with advanced laryngeal or hypopharyngeal squamous cell carcinoma submitted to total laryngectomy or pharyngolaryngectomy and thyroidectomy; to determine whether clinic-pathological characteristics can predict glandular involvement. Methods: A retrospective case series with chart review, from January 1998 to July 2013, was undertaken in a tertiary care university medical center. An inception cohort of 83 patients with larynx/hypopharynx squamous cell carcinoma was considered. All patients had advanced stage disease (clinically T3-T4) and underwent total laryngectomy or total pharyngolaryngectomy in association with thyroidectomy. Adjuvant therapy was indicated when tumor or neck conditions required. Frequency of thyroid cartilage invasion was calculated; univariate and multivariate analysis of demographic, clinical and pathological characteristics associated with cartilage invasion were performed. Results: The overall frequency of invasion of the thyroid gland was 18.1%. Glandular involvement was associated with invasion of the following structures: anterior commissure (odds ratio = 5.13; 95% confidence interval 1.07-24.5), subglottis (odds ratio = 12.44; 95% confidence interval 1.55-100.00) and cricoid cartilage (odds ratio = 15.95; 95% confidence interval 4.23-60.11). Conclusions: Invasion of the thyroid gland is uncommon in the context of laryngopharyngeal squamous cell carcinoma. Clinical and pathological features such as invasion of the anterior commissure, subglottis and cricoid cartilage are more associated with glandular invasion.